Application of Dialectometry to Nova Scotia Acadian French dialects: phonological distance. - Flikeid, Karin; Cichocki, Wladyslaw (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
This paper presents a preliminary application of Dual Scaling to the measure of phonological distance among dialects of Acadian French spoken in Nova Scotia. The application differs somewhat from previous ones in that it borrows the notion of linguistic variable from Labovian sociolinguistics in establishing linguistic distance. The raw data are from Flikeid's dialectological survey of Nova Scotia Acadian French. Sixty-six subjects from the five major French-speaking regions were chosen, and phonological variables were established. Dual Scaling was used to produce a graphical representation which identifies the major phonological and social patterns in the data. The results illustrate the role of geographic and stylistic variables in determining and explaining the phonological distance among the dialects.